Bad Practices in Governance and Bleaching of Palm Oil Land with Potential Losses to the State - Khoeriyah, Siti; Juwita, Aulia Hapsari (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The enactment of the Job Creation Law provides an opportunity for bad governance practices through changes to technical forest management regulations, so that this creates potential losses for the state. This research aims to analyze potential state losses due to changes in regulations for managing palm oil plantations in forest areas in Riau Province. Analysis of potential state losses was carried out by calculating the losses incurred by 7 palm oil companies in Riau Province operating in forest areas. The research method used is analysis of the calculation of Non-Tax State Revenue (PNBP) from the results of the Forest Resources Provision (PSDH). Based on the results of the analysis, the potential state loss due to this regulatory change reaches IDR 875,732,734,813. The bleaching of oil palm land in forest areas through forest release by the government worsens existing governance practices. The new regulations that have been established still favor economic interests while ignoring the sustainability of forest and environmental resources. Based on this, the policy directions that can be implemented include strengthening institutions and multi- level governance, improving long-term strategies for smallholder palm oil, building local and international research partnerships, designing sustainable development policy models that do not only focus on poverty alleviation, and review the application of company sanctions based on Minister of Environment and Forestry Decree No. 661 of 2023